Affiliation to Social Security of Employees and its Effects on the Finances of Companies in Mexico - Tosca Vidal, Carlos Mauricio; Martínez Prats, Germán; Guzman Fernandez, Candelaria (Universidad Pedagógica y Tecnológica de Colombia, 2021)
The objective of this paper is to determine the consequences of the affiliation of employees to the social security system with a lower salary than the real one in Mexico. There is little literature about the effect of these bad practices. A descriptive investigation was carried out both from the legal -as regard sanctions-, and financial point of view -as it affects the owners of the organizations. It has a qualitative approach and a documentary technique. From the investigation it was determined that there are multiple affected: State, employees and employer. The State, because it stops receiving 43% of the Social Security contributions; the employee, because upon having an accident or disability, the State through the Social Security Institute grants his benefits according to the salary with which he is registered; and the employer, because if the employee is injured, that one has the obligation to pay the missing benefits, for which this employer must form a constituent capital. It is concluded that employers must take into account all the consequences of reducing employees' wages when registering them in social security, because they put the finances of the organization at risk and can be sentenced to deprivation of liberty (e.g. imprisonment) for leaving the employee defenseless.